2013
DOI: 10.1177/0264619612465168
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of an emotional support and counselling service for people with visual impairments

Abstract: There is growing evidence of the need for services to address the emotional support needs of people with visual impairments. This paper presents findings from a mixed methods evaluation of an emotional support and counselling (ESaC) service delivered within an integrated low vision service, focusing primarily on the qualitative findings. Data collected using a standardised measure of psychological well-being (the CORE-OM) show an improvement in the psychological well-being of clients of the service between bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Positive or negative mechanisms of adjustment, also termed coping strategies, can help individuals to master their impairment. Broadly speaking, we can distinguish between adaptive coping strategies such as seeing a counsellor and goal setting or maladaptive coping strategies including social withdrawal and substance misuse [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positive or negative mechanisms of adjustment, also termed coping strategies, can help individuals to master their impairment. Broadly speaking, we can distinguish between adaptive coping strategies such as seeing a counsellor and goal setting or maladaptive coping strategies including social withdrawal and substance misuse [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brojna istraživanja su pokazala da su deca sa ošte-ćenjem vida izloženija riziku od socijalne izolacije (Hodge, et al, 2013). Prilagođavanje na zahteve života je, u svetu koji je vizuelno orijentisan, veoma kompleksno za osobe sa oštećenjem vida (Schinazi, 2007).…”
Section: Socijalne Veštineunclassified
“…According to last available global estimates 285 million people in general population had problems with sight and 39 million of them were blind [ 17 ]. VI has a significant negative impact on the emotional, physical and social life domains, as well as work-related aspects [ 18 , 19 ]. A Polish report on the QoL of people with VI found that about 60% of respondents were satisfied with their lives and a stable job was recognized as an indicator of happiness by more than half [ 20 ].…”
Section: Introductionmentioning
confidence: 99%